2016
DOI: 10.1086/687842
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of metabolic rates among macrophyte and nonmacrophyte habitats in streams

Abstract: Little is known about the relative contribution of different stream habitats to reach-scale metabolism. We measured in situ metabolism in sand, gravel, stone, and macrophyte habitats to compare metabolic rates among these habitat types and to compare habitat-weighted measurements with reach-scale measurements. We used open-bottom chambers in sand, gravel, and macrophyte habitats and closed-bottom chambers in stones, and we estimated reach-scale metabolism from 2-station O 2 budgets. Macrophyte habitats had a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…We saw that GPP was highest in spring and summer and lower in autumn, whereas ER was low in spring, but high in summer and autumn. Reach-scale N uptake was below detection (BD) in autumn, and heterotrophic assimilation was low in spring (and therefore difficult to visualise on the plot, although the relative contributions are included in the figure) in epiphytic biofilms colonising macrophytes (Alnoe, Riis, & Baattrup-Pedersen, 2016;Levi et al, 2015), while benthic biofilms may be less prevalent as a result of macrophyte shading. This counter-intuitive outcome may be explained by several mechanisms.…”
Section: Links Between Seasonal Macrophyte Biomass Transient Storamentioning
confidence: 99%
See 1 more Smart Citation
“…We saw that GPP was highest in spring and summer and lower in autumn, whereas ER was low in spring, but high in summer and autumn. Reach-scale N uptake was below detection (BD) in autumn, and heterotrophic assimilation was low in spring (and therefore difficult to visualise on the plot, although the relative contributions are included in the figure) in epiphytic biofilms colonising macrophytes (Alnoe, Riis, & Baattrup-Pedersen, 2016;Levi et al, 2015), while benthic biofilms may be less prevalent as a result of macrophyte shading. This counter-intuitive outcome may be explained by several mechanisms.…”
Section: Links Between Seasonal Macrophyte Biomass Transient Storamentioning
confidence: 99%
“…For example, 24% of primary production in a macrophyte habitat was due to epiphytic microalgae (Alnoe et al, 2016); this contribution can be even higher when macrophytes themselves are light-limited, and their role as substrate for epiphytic biofilm increases. Therefore, in this study, the difference in spring and summer GPP might have been due to the increased role of benthic biofilm plus macrophytes in spring, whereas the fully developed epiphytic and benthic biofilm, without significant macrophyte contribution, in summer may have resulted in lower reach-scale GPP.…”
Section: Links Between Seasonal Macrophyte Biomass Transient Storamentioning
confidence: 99%
“…Raz transformation was also positively correlated with chlorophyll a and GPP, indicating that the contribution of autotrophic respiration to ER increased predictably with algal biomass. A recent meta‐analysis similarly reported that respiration increased with autotrophic biomass and GPP (Alnoee, Riis, & Baattrup‐Pedersen, ).…”
Section: Discussionmentioning
confidence: 87%
“…Likewise, aquatic vegetation abundance may stimulate heterotrophic metabolism by providing substrate for epiphytic biofilms in the water column, and by supplying and trapping organic matter. A literature review by Alnoee et al [] showed positive correlations between autotrophic biomass and primary production and respiration, while O'Brien et al [] found that primary production, but not ecosystem respiration, was closely correlated with macrophyte cover. Our results of daily rates of GPP agree with these findings, with higher rates in mesocosms with higher water depths and coverage of aquatic vegetation (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, our study is not able to directly distinguish the relative importance to observed metabolic activity of the contribution of the aquatic vegetation itself from that of associated epiphytic biofilms, nor the relative importance of the vegetated surface water from that of hyporheic sediments. Nevertheless, stream sections dominated by aquatic vegetation have been shown to have higher metabolic activity than those dominated by sediment, in large part due to epiphytic biofilms associated with the vegetation [ Alnoee et al ., ]. Given the high surface area of Ranunculus , the dominant vegetation type in our mesocosms, the contribution of epiphytes to observed metabolic activity could likewise be high.…”
Section: Discussionmentioning
confidence: 99%